Fabrication of conjugated microporous polytriazine nanotubes and nanospheres for highly selective CO2 capture. Issue 29 (29th March 2017) - Wang, Zhiqiang; Liu, Junling; Fu, Yu; Liu, Cheng; Pan, Chunyue; Liu, Zhiyong; Yu, Guipeng
Abstract : A new strategy for fabricating CMPs with a controllable morphology and a molecular design for enhancing host–guest interactions lead to high capacities for CO2 and exceptionally high ideal selectivities over N2 . Abstract : A one-spot template approach for fabricating porous organic nanotubes was developed and a molecular design, i.e. introducing thiophene and s-triazine functionalities to enhance host–guest interactions, lead to novel porous solids with high capacities for CO2 and exceptionally high ideal selectivities over N2 for effective gas storage and separation.